The dynamics of Quiet Eye under stress in elite table tennis performance - Vincze, A.; Jurchis, R.; Iliescu, D. (International Journal of Sport and Exercise Psychology, 2023)
Quiet Eye (QE) has been accounted as a mechanism that contributes to visuomotor coordination, an important process in athletic performance. QE is defined as the final fixation on a specific location or object in the visuomotor workspace, within 3° of visual angle, for a minimum of 100 ms that enables the athletes to gather relevant information before a critical movement. Several lines of research have shown that QE is affected by stress and that this alteration further leads to decreased task performance. The present study determined whether stress affects QE in elite table tennis performance. Athletes performed a table tennis exercise in which they had to hit a sequence of 100 balls. Each athlete underwent the exercise in a stressful condition and in a non-stressful one, while gaze behaviour was captured using Tobii Glasses 2 eye tracking system. We first found that athletes made longer QE before successfully hit balls than before missed balls, confirming that longer QE supports accuracy. More importantly, QE and performance decreased in the stressful condition, but athletes still displayed longer QE durations in hit, compared to missed balls under stress. The present results show that stress affects QE and, subsequently, performance, but also that better performance under stress is associated with longer QE duration.